A metáfora antropofágica em Todas as vezes que dissemos adeus de Kaká Werá Jecupé - Cunha Ramos Quaresma, Carline (Tusaaji: A Translation Review, 2018)
As one of the first Indigenous authors in Brazil to record the myths of his own people in book form, Kaká Werá Jecupé occupies a privileged space of enunciation vis-à-vis other writers who have published books about Indigenous verbal arts. His books rescue the ancestral memory of the Guarani people and carry with them the differential of having been written by someone who belongs to this culture. According to Kaká Werá Jecupé, until the publication, in 1994, of the first edition of Todas as vezes que dissemos adeus, Brazilian Indigenous culture had always been presented through the voices of anthropologists, indigenists, or social scientists. In this paper I focus on the resonances in the book of the anthropophagy metaphor—a trace of Indigenous culture drawn by Oswald de Andrade as a political gesture for a discussion of questions of the relationship between self and other. I take it as a point of departure to discuss Kaká Werá Jecupé’s position, living "between two worlds", and his mission to reveal his age-old tradition to so-called civilization, promoting the opening of a dialogue between cultures.